2009
DOI: 10.1016/j.jjcc.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Progressive atrial lead perforation developed 5 years after pacemaker replacement

Abstract: This report describes an asymptomatic case of atrial lead perforation which developed 5 years after pacemaker implantation. Although retrospective findings of computed tomography showed a screw-in atiral lead had already perforated 9 months after the implantation, the lead protrusion on chest X-rays and pacing failure had not been noticed until another 3 years later. At first, this complication was managed conservatively, however, a lead perforation progressively developed and, as a result, open surgery was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Previous case reports have described perforating leads migrating into the pleural cavity, peritoneal cavity, or to the chest wall . Given the potential occurrence of a progressive protrusion of a culprit lead, lead revision is mandatory in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports have described perforating leads migrating into the pleural cavity, peritoneal cavity, or to the chest wall . Given the potential occurrence of a progressive protrusion of a culprit lead, lead revision is mandatory in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective review of our patient’s records revealed that the correct diagnosis had been missed on prior CXRs and CT scans. In a similar reported case, an atrial lead protrusion was diagnosed 5 years after lead implantation 13 . Retrospective CT scan examination showed that the perforation had been present 4 years earlier.…”
Section: Discussionmentioning
confidence: 65%
“…If the defect caused by perforation of the cardiac wall is small and plugged immediately due to cardiomyocyte contraction, then a pericardial effusion is avoided and the pneumothorax can be stabilized. A larger cardiac perforation can lead to pericarditis, pericardial effusion, tamponade, hemodynamic instability [14] and even death; pleuritis, chest pain, dyspnea, hypotension, and syncope [12,[15][16][17][18], abnormal pacemaker function (primarily a high threshold or loss of capture) [9, 11-12, 14-17, 19] and extracardiac pacing (diaphragmatic, pectoralis or intercostal muscle stimulation [14][15]19] and inappropriate shock [17]. Pneumopericardium and pneumothorax and pleural effusion are very rare complications [3, 6-9, 15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Perforation, with the lead or the helix outside the cardiac silhouette, can be diagnosed by means of fluoroscopy, chest radiography, and echocardiography [14,19], but these methods are not reliable for evaluating less severe lead perforation [8-9, 17, 20]. The diagnostic gold standard is ECG-gated highresolution computed tomography (HRCT) [9], which has optimal demarcation of the interface between the myocardium, blood, and fat [12,15,[17][18][19][20], although star artifacts from the pacemaker wire sometimes make it difficult to precisely identify the lead tip [8-9, 17, 19-20], and there is a risk of over-diagnosing perforation [16]. Apart from aiding in making the diagnosis HRCT also helps in planning lead retrieval as it gives a good assessment of the orientation of vital structures around the displaced lead [9,16].…”
Section: Discussionmentioning
confidence: 99%